Femoral vein injury from a trochanteric hip fracture. Issue 6 (June 2015) - Medlock, G.; McCullough, L.; Barker, S.
Abstract: A case of a comminuted trochanteric fracture where the lesser trochanteric fragment had displaced significantly injuring and becoming lodged within the common femoral vein.